REPRESENTASI RUANG DAN TOKOH PELACUR DALAM PROSA INDONESIA MODERN - Dheny jatmiko (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
This article discusses the representation of space and prostitute characters in Indonesianmodern prose. The data were taken from Bumi Manusia, Kembang Jepun, Perempuan Kembang Jepun,Kremil, and Existere. The discussion aims at reconstructing prostitution in Surabaya and analyzing theprostitution related to the social, economic, and political problems. Bumi Manusia portrays a prostitutionmanaged by a Chinese in the era of Dutch colonization. Kembang Jepun and Perempuan Kembang Jepuntaken the colonial time and Japanese occupation as the setting of the novels describes the relationshipbetween prostitution and political issues such as anti-colonial movements and independent struggle. InKremil whose setting is 1960s, one can read the relationship between prostitution and the tragedy of PKI(Indonesian Communist Party). Existere portrays the prostitution in Dolly.Key words: Representasi, Sastra Bandingan, Pelacuran, Surabaya